Work attitude and job-related stress among teachers in kindergarten - Padillo, Gengen G.; Jalalon, Hannah Jane T.; Cherreguine, Josery B.; Mejias, Marife B.; Manguilimotan, Ramil P. (International Journal of Social and Management Studies, 2024)
This study determined the work attitude and job-related stress among kindergarten teachers in theidentified schools in Cebu. The quantitative research method using an adapted survey questionnaire wasemployed for Kindergarten teachers who were selected using convenience sampling to determine thedemographic profile of the respondents in terms of age and gender, civil status, health history, role in thefamily, number of hours per week, combined monthly family income, highest educational attainment, anddistance from residence to work; degree of job-related stress encountered by the participants; degree of work-related attitude of the respondents, and a correlational analysis between respondents’ profile and the job-related stress and respondents’ profile and work-related attitude. Gathered data were treated using frequencycount, percentage, weighted mean, t-test, and chi-square. Findings revealed that teachers were very satisfiedwith their relationships and experienced minimal job-related stress. Moreover, they were satisfied andexperienced occasional stress in their job, roles, career development, and organization. On the contrary, theyexperienced high levels of job-related stress in the home/work interface. In addition, findings indicate thatteachers exhibit positive attitudes toward their work. A correlation analysis revealed that age, role, andeducational attainment have a significant relationship with job-related stress, while the degree of sufficiency ofthe family income has a significant relationship with job and role. Consequently, the home/work interfaceshowed no significant relationship between work attitude and job-related stress. Hence, it is recommended thata crafted action plan be adopted for implementation to address the work-related stress among KindergartenTeachers.